2019
DOI: 10.1038/s41598-019-40904-z
|View full text |Cite
|
Sign up to set email alerts
|

Low Electric Treatment activates Rho GTPase via Heat Shock Protein 90 and Protein Kinase C for Intracellular Delivery of siRNA

Abstract: Low electric treatment (LET) promotes intracellular delivery of naked siRNA by altering cellular physiology. However, which signaling molecules and cellular events contribute to LET-mediated siRNA uptake are unclear. Here, we used isobaric tags in relative and absolute quantification (iTRAQ) proteomic analysis to identify changes in the levels of phosphorylated proteins that occur during cellular uptake of siRNA promoted by LET. iTRAQ analysis revealed that heat shock protein 90 (Hsp90)α and myristoylated alan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…However, detailed cellular mechanisms for positive effects by ET onto brain remain largely unclear. Our previous and present studies demonstrated that ET induces activation of intercellular signaling such as Rho GTPase via HSP90 and PKC [22], and also increases the secretion of EV from cultured cells. Although the effect of ET on brain-derived cells are needed to be examined in future, ET-mediated intracellular signaling activation and increase of EV secretion may have the potential to be involved in beneficial effects of tDCS in the brain.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…However, detailed cellular mechanisms for positive effects by ET onto brain remain largely unclear. Our previous and present studies demonstrated that ET induces activation of intercellular signaling such as Rho GTPase via HSP90 and PKC [22], and also increases the secretion of EV from cultured cells. Although the effect of ET on brain-derived cells are needed to be examined in future, ET-mediated intracellular signaling activation and increase of EV secretion may have the potential to be involved in beneficial effects of tDCS in the brain.…”
Section: Discussionmentioning
confidence: 91%
“…Since our previous study demonstrated that ET of cultured cells induces endocytosis of macromolecules via activation of Rho GTPase [22], we evaluated the influence of Rho GTPase inhibition on ET-mediated increase in EV secretion by using a Rho GTPase inhibitor, Rhosin hydrochloride [26]. The results showed that increase in the particle number of the collected EVs from 3T3 Swiss Albino cells treated by low level electricity was hardly inhibited by the Rho GTPase inhibitor (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations